2007
DOI: 10.1021/bc0700943
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Lipopolyplexes Using Bifunctional Peptides Incorporating Hydrophobic Spacer Amino Acids: Synthesis, Transfection, and Biophysical Studies

Abstract: We have developed efficient synthetic routes to two hydrophobic amino acids, suitably protected for solid-phase peptide synthesis, and have successfully synthesized peptides containing these or other hydrophobic amino acids as spacers between a Lys16 moiety and an integrin-targeting motif. These peptides have in turn been used to formulate a range of lipopolyplex vectors with Lipofectin and plasmid DNA. The transfection efficiencies of these vectors and their aggregation behavior in buffers and in serum have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…A synthetic gene delivery system has previously been described comprising a mixture of cationic lipid (L), an integrin-targeting peptide (P) and plasmid DNA (D) which, when combined electrostatically, forms LPD complexes with highly synergistic properties and transfection efficiencies that were orders of magnitudes higher than the equivalent lipid:DNA (LD) or peptide:DNA (PD) complexes. Significantly LPD complexes prepared using the lipids DOTMA ( 1 ) and DOPE ( 2 ) in a 1:1 weight ratio and incorporating a targeting peptide were also able to transfect nondividing cells . Furthermore the LPD complexes exhibited low toxicity and immunogenicity when examined in vitro and in vivo. ,, Fluorescence quenching and fluorescence correlation spectroscopy (FCS) measurements have suggested that the structure of similar integrin targeting LPD vectors possessed a tightly bound DNA–peptide core surrounded by a lipid layer from which (at least some of) the cyclic integrin domain protrudes …”
Section: Introductionmentioning
confidence: 99%
“…A synthetic gene delivery system has previously been described comprising a mixture of cationic lipid (L), an integrin-targeting peptide (P) and plasmid DNA (D) which, when combined electrostatically, forms LPD complexes with highly synergistic properties and transfection efficiencies that were orders of magnitudes higher than the equivalent lipid:DNA (LD) or peptide:DNA (PD) complexes. Significantly LPD complexes prepared using the lipids DOTMA ( 1 ) and DOPE ( 2 ) in a 1:1 weight ratio and incorporating a targeting peptide were also able to transfect nondividing cells . Furthermore the LPD complexes exhibited low toxicity and immunogenicity when examined in vitro and in vivo. ,, Fluorescence quenching and fluorescence correlation spectroscopy (FCS) measurements have suggested that the structure of similar integrin targeting LPD vectors possessed a tightly bound DNA–peptide core surrounded by a lipid layer from which (at least some of) the cyclic integrin domain protrudes …”
Section: Introductionmentioning
confidence: 99%
“…Our previous results had also shown that vectors containing peptides incorporating linkers that are partly hydrophobic demonstrated improved transfection properties, which is likely due to the improved accessibility of the integrin-binding motif. 46 We also hypothesized that, by adding the cleavable linker RVRR in KG32, as is the case in peptide ME27, this would promote processing of peptide components of receptor-targeted nanocomplex formulations. RVRR peptide motifs are cleavable by the endosomal enzymes furin and cathepsin B.…”
Section: Discussionmentioning
confidence: 99%
“…The use of these compounds in hybrid materials increases the biocompatibility of such systems and allows interactions with biological organisms, which is advantageous for bioresorbable sutures, screws or plates, tissue engineering scaffolds and drug delivery systems. [32][33][34] If amino acids are used as a modier for organo-modication of clays, they can be expected to be compatible with a protein/biopeptide matrix. When compared with a chemically synthesized modier, amino acid biosurfactants have the important advantages of biodegradability, low toxicity and various possible structures.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…When compared with a chemically synthesized modier, amino acid biosurfactants have the important advantages of biodegradability, low toxicity and various possible structures. [32][33][34] In this study, a Cloisite-Val organoclay was prepared via a simple and environmentally friendly ion-exchange method in aqueous solution. Our interest in applying an amino acid as a swelling agent stems from the fact that the amine group of an amino acid can provide a cation (-NH 3 + ) which can form an ionic bond with the negatively charged silicate layers of MMT as well as an electrostatic interaction and covalent bond with DNA chains for the construction of DNA-based biosensors.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%